Elucidating white matter changes of association fibres and cerebellum in noise-induced hearing loss: A diffusion tensor imaging study - Mohd Khairul Izamil, Zolkefley; Norhidayah, Abdull; Rajeev Shamsuddin, Perisamy; Muzaimi, Mustapha; Daud, Adam; Muhamad Ariff, Muhamad Noordin (Association for Computing Machinery, 2024)
This study investigates the impact of Noise-Induced Hearing Loss (NIHL) on the structural integrity of white matter pathways in the brain, specifically focusing on association fibers and the cerebellum. Utilising Diffusion Tensor Imaging (DTI) technique, this study examines changes in white matter integrity that may underlie cognitive and perceptual deficits associated with NIHL. Findings suggest alterations in the association fibers and cerebellum, indicating potential disruptions and neuroplasticity changes in auditory processing and cognitive functions. This research contributes to understanding the neurobiological effects of NIHL, offering insights for therapeutic strategies targeting auditory rehabilitation and cognitive impairment.